Designing a module for improving communication skills amongst interns in a surgical setting - Krishnappa, Rohit; Rajagopalan, S. (International Surgery Journal, 2020)
Background: Healthcare professionals are at the receiving end of a large number of violent incidents directed against them. One of the reasons cited is the abysmal levels of communication skills of young qualified doctors. We feel there is an urgent need for training them in this area of behavioral skill. Methods: It was a quantitative interventional study. We measured the communication skills before and after training, by a scale devised for the study and pre validated by peers and piloted as a project. Results: The training is effective in improving their knowledge and communication skills giving them confidence to face the challenges of day to day clinical work in surgical setting. Conclusions: This small training module on consent taking needs to be incorporated in the internship training. Faculty need to be sensitised regarding improvement of communication skills and knowledge of the students by adopting this training module and workplace based assessment for all surgical interns.